A new freshwater amphipod species, Gammarus topkarai sp. nov., from Turkey (Amphipoda: Gammaridae), with a key for Turkish freshwater Gammarus species - Özbek, Murat; Balik, Suleyman (Zootaxa, 2009)
A new species of freshwater Amphipod, Gammarus topkarai sp. nov., collected from Ivriz Creek, Tarsus Province, South Anatolia, is described and illustrated. The new species belongs to Gammarus pulex-group and shows similar characteristic features with Gammarus agrarius G. S. Karaman, 1973. Absence of well developed dorsal elevations on the urosome segments, smaller body length and relatively lower endopod/exopod ratio of third uropod are the most obvious features differ from G. agrarius. A detailed morphological description and illustrations of new species are given and differences from related species are discussed. An updated identification key of Gammarus taxa reported from Turkey, up to date, was also presented.